Efficient and Cost-Effective Alternative Treatment for Recurrent Urinary Tract Infections and Interstitial Cystitis in Women: A Two-Case Report. (21st December 2014) - Mansour, Anthony; Hariri, Essa; Shelh, Samar; Irani, Ralph; Mroueh, Mohamad
Abstract : Urinary tract infections (UTIs) are among the most common bacterial infections affecting women. UTIs are primarily caused by Escherichia coli, which increases the likelihood of a recurrent infection. We encountered two cases of recurrent UTIs (rUTIs) with a positive E. coli culture, not improving with antibiotics due to the development of antibiotic resistance. An alternative therapeutic regimen based on parsley and garlic, L-arginine, probiotics, and cranberry tablets has been given. This regimen showed a significant health improvement and symptoms relief without recurrence for more than 12 months. In conclusion, the case supports the concept of using alternative medicine in treating rUTI and as a prophylaxis or in patients who had developed antibiotic resistance.